Specificity of DNA import into isolated mitochondria from plants and mammals - Koulintchenko, M.V.; Ibrahim, N.; Klimenko, E.S.; Konstantinov, Yu.M.; Weber-Lotfi, F.; Dietrich, A. (Вiopolymers and Cell, 2014)
Aim. Investigation of different features of DNA import into plant and human mitochondria, for a better understanding of mitochondrial genetics and generation of biotechnological tools. Methods. DNA up-take experiments with isolated plant mitochondria, using as substrates various sequences associated or not with the specific terminal inverted repeats (TIRs) present at each end of the plant mitochondrial linear plasmids. Results. It was established that the DNA import efficiency has a non-linear dependence on DNA size. It was shown that import into plant mitochondria of DNA molecules of «medium» sizes, i. e. between 4 and 7 kb, barely has any sequence specificity: neither TIRs from the 11.6 kb Brassica plasmid, nor TIRs from the Zea mays S-plasmids influenced DNA import into Solanum tuberosum mitochondria. Conclusions. The data obtained support the hypothesis about species-specific import mechanism operating under the mitochondrial linear plasmids transfer into plant mitochondria. Мета. Вивчення відмінностей в імпорті ДНК у мітохондрії рослин і людини для кращого розуміння генетики мітохондрій та розробки біотехнологічних підходів до її дослідження. Методи. Експерименти з імпорту ДНК в ізольоовані мітохондрії рослин з використанням як субстратів послідовностей, які містять або не містять специфічних кінцевих інвертованих повторів (КІП), характерних для лінійних плазмід рослинних мітохондрій. Результати. Встановлено, що ефективність імпорту ДНК у мітохондрії нелінійно залежить від розміру ДНК. Показано, що імпорт у рослинні мітохондрії молекул ДНК «середніх» розімрів (4–7 тис. п. н.) має незначну структурну специфічність: ані КІП плазміди 11,6 тис. п. н. з Brassica napus, ані КІП S-плазмід із Zea mays не чинять впливу на імпорт ДНК у мітохондрії Solanum tuberosum. Висновки. Отримані дані свідчать на користь гіпотези існування видоспецифічного механізму перенесення мітохондріальних лінійних плазмід у рослинні мітохондрії. Цель. Изучение различных свойств импорта ДНК в митохондрии растений и человека для лучшего понимания генетики митохондрий и разработки биотехнологических подходов для ее исследования. Методы. Эксперименты по импорту ДНК в изолированные митохондрии растений с использованием в качестве субстратов последовательностей, содержащих или не содержащих специфических концевых инвертированных повторов (КИП), характерных для линейных плазмид растительных митохондрий. Результаты. Установлено, что эффективность импорта ДНК в митохондрии имеет нелинейную зависимость от размера ДНК. Показано, что импорт в растительные митохондрии молекул ДНК «средних» размеров (4–7 тыс. п. н.) имеет незначительную структурную специфичность: ни КИП плазмиды 11,6 тыс. п. н. из Brassica napus, ни КИП S-плазмиды из Zea mays не оказывают влияния на импорт ДНК в митохондрии Solanum tuberosum. Выводы. Полученные данные свидетельствуют в пользу гипотезы существования видоспецифического механизма переноса митохондриальных линейных плазмид в растительные митохондрии.